2017
DOI: 10.5937/ffr1701065s
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement of gluten-free bread based on soybean and enriched with sugar beet molasses

Abstract: ABSTRACT:The aim of this work was to improve the quality of gluten-free bread made with high content of soy flour and enriched with sugar beet molasses by incorporating ingredients with a potential to simultaneously enhance the nutritional quality of the breads. The following ingredients were used: pea protein isolate, pea fibre and chia seeds. The chosen ingredients exerted positive effects on bread quality. They promoted volume increase and crumb softening. In this respect, the most effective ingredients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It was reported that molasses of sugar beet was used by microorganisms as sugar source for xanthan fermentation and, consequently, that xanthan obtained was used as a thickener in food industry (Moosavi and Karbassi, 2010). It was also reported that molasses of beet sugar was used in the production of various products for human nutrition such as cookie (Filipčev et al, 2012;Filipčev et al, 2014), bread (Filipčev et al, 2010Filipčev, 2011), gluten-free product (Šimurina et al, 2008;Filipčev et al, 2016;Šimurina et al, 2017), ice-cream (Acan et al, 2020), probiotic yoghurt (Ghazal andAtallah, 2016). However, as a result of the literature reviews carried out, it was not met any studies regarding that molasses of beet sugar was used in meat products.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that molasses of sugar beet was used by microorganisms as sugar source for xanthan fermentation and, consequently, that xanthan obtained was used as a thickener in food industry (Moosavi and Karbassi, 2010). It was also reported that molasses of beet sugar was used in the production of various products for human nutrition such as cookie (Filipčev et al, 2012;Filipčev et al, 2014), bread (Filipčev et al, 2010Filipčev, 2011), gluten-free product (Šimurina et al, 2008;Filipčev et al, 2016;Šimurina et al, 2017), ice-cream (Acan et al, 2020), probiotic yoghurt (Ghazal andAtallah, 2016). However, as a result of the literature reviews carried out, it was not met any studies regarding that molasses of beet sugar was used in meat products.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, molasses was added to some food formulations as biscuits and cookies (Šimurina et al , ; Filipčev et al , ; Filipčev et al , ), bread (Filipčev et al , ) and gluten‐free baked foods (Filipčev et al , , ; Šimurina et al , ). Despite the product trials, molasses was used in the literature previously as a honey replacer (Filipčev et al , ), flavour and nutritional value improver (Šimurina et al , ) and a sweetener (Šimurina et al , ). In our knowledge, there is not any study in which sugar beet or cane molasses is dried by spray drying for using as a food ingredient, for example as a bulking agent.…”
Section: Introductionmentioning
confidence: 99%